The enhanced performance of ceria by HF treatment for selective catalytic reduction of NO with NH3. (1st September 2016) - Yang, Ning-zhi; Guo, Rui-tang; Tian, Yuan; Pan, Wei-guo; Chen, Qi-lin; Wang, Qing-shan; Lu, Chen-zi; Wang, Shu-xian
Graphical abstract: Highlights: The SCR activity of CeO2 catalyst is greatly enhanced by HF treatment. The enhanced surface acidity of CeO2 -F is the main reason for its high SCR activity. The NH3 -SCR reactions on CeO2 and CeO2 -F mainly follow the Eley-Rideal mechanism. Abstract: The effect of HF treatment on the performance of ceria for selective catalytic reduction of NO with NH3 was investigated in this study. The experimental results showed that HF treatment could greatly enhance the SCR performance of ceria within the temperature range of 100–400 °C. From the characterization results of Brunauer–Emmett–Teller (BET), X-ray diffraction (XRD), temperature programmed reduction of hydrogen (H2 -TPR), temperature programmed desorption of ammonia (NH3 -TPD) and X-ray photoelectron spectroscopy (XPS), the good performance of HF-treated ceria may be attributed to its lower crystallinity, better reducibility, higher NH3 adsorption capacity, and the enrichment of surface chemisorbed oxygen. And the results of in situ DRIFT study indicate that the NH3 -SCR reactions on CeO2 and CeO2 -F mainly follow the Eley–Rideal mechanism.